Staining method for coronary arteries - E. G. Dmitrieva; S. L. Khatsko; A. A. Yakimov (Сибирский научный медицинский журнал)
Detection of elastic and collagen fibers in the same histological section to determine their relationships and quantification is important for connective tissue investigations. The aim of the study was to assess the possibility of differentiated staining of elastic and collagen fibers with resorcin-fuchsin and fast green FCF in the same histological section and compare the result of this method with the results of the classical methods of staining connective tissue, performed according to standard protocols. Material and methods. We studied adult human hearts, obtained from patients who died from non-cardiac causes. We cut tissue sections from the anterior interventricular artery and the underlying myocardium. After formalin fixation, standard processing and embedding in paraffin of the material, histological sections were made. Histological sections were deparaffinized and immersed resorcin-fuchsin for 15 minutes, then stained with Weigert’s iron hematoxylin for 2 minutes, then for 2 minutes were applied to the preparation surface 0.1% solution of fast green FCF mixed with a saturated solution of picric acid immediately before staining in a ratio of 1:10, the histological sections were dehydrated, cleared and mounted in permanent mounting medium. Results. Elastic fibers were dyed in dark blue, and collagen fibers in different shades of green, which made it possible to differentiate them on the basis of color differences in one histological section. Conclusion. We have developed and tested the method of staining, which provides the possibility of simultaneous detection of elastic and collagen fibers with successive staining with solutions of resorcin-fuchsin and fast green FCF on one histological section.